Challenges of managing patients with mechanical heart valve thrombosis in pregnancy: A case series - Hoevelmann, Julian; Sliwa, Karen; Chin, Ashley; Viljoen, Charle (SA Heart Journal, 2022)
Mechanical valve thrombosis is a feared complication in pregnant women with mechanical heart valves (MHV). It is associated with a high maternal and foetal morbidity and mortality. Optimal anticoagulation strategies for pregnant women with MHV remain controversial. Vitamin K antagonists (VKA) are the most effective treatment regimen to prevent valve thrombosis and are therefore considered the safest treatment for the mother. However, VKAs increase the risk of embryopathy, foetopathy, foetal haemorrhage and foetal loss. A particular challenge is to balance the need for adequate anticoagulation for MHV during pregnancy against the risk of bleeding, teratogenicity and fetotoxicity. In this case series, we describe complexity of the management of anticoagulation in pregnant patients with MHV, and describe 2 treatment approaches in patients with MHV thrombosis. Our case series high-lights that anticoagulation strategy should be individualised, and that best management is provided by a multidisciplinary cardio-obstetric team.